Revamping world trade. - NOYELLE, Thierry (1994)
Asserts that whether developing countries reap all the benefits they should from the results of the Uruguay Round will depend on how well they negotiate additional hurdles in the months and years ahead. These include not only strengthening their access to markets in the North, but also obtaining a renewed commitment from the developed countries to support the process of structural adjustment in the South.